The economic benefit of agarwood production through aeration method into the Aquilaria malaccensis tree in Bangladesh - Chowdhury, M; Rahman, A; Hussain, MD; Kabir, E (Bangladesh Journal of Agricultural Research, 2017)
Abstract not available Bangladesh J. Agril. Res. 42(1): 191-196, March 2017